Low Birth Weight, Birth Order, URTI, and Unimproved Latrines as Risk Factors for Growth Faltering in Rural Eastern Indonesia - Gandha Sunaryo Putra; Suhartono Suhartono; Cahya Tri Purnami; Martha Irene Kartasurya (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2026)
Background: Growth faltering in children remains a major global public health concern because its consequences extend far beyond early life, affecting cognitive development and future economic well being. In Indonesia, children living in rural settings face a greater risk of experiencing growth problems, particularly in contexts marked by infectious diseases, inadequate sanitation, and maternal related factors. This study was conducted to examine the risk factors associated with growth faltering among children under two years of age in rural areas of Eastern Indonesia using data from the 2023 Indonesian Health Survey. Method: A cross sectional design was applied, involving 2,672 children aged 6 to 23 months. Data were analyzed using the chi square test and multiple logistic regression Result: The findings revealed that a history of low birth weight (AOR = 2.45; 95% CI: 1.755–3.434; p < 0.00), birth order (AOR = 1.23; 95% CI: 1.031–1.481; p = 0.015), a history of upper respiratory tract infection (AOR = 1.28; 95% CI: 1.04–1.57; p = 0.020), and unimproved latrine conditions (AOR = 1.314; 95% CI: 1.046–1.651; p = 0.019) were significant risk factors for growth faltering. Conclusion: These results suggest that infectious diseases, poor sanitation, and maternal characteristics play a central role in shaping the burden of child growth faltering in rural Eastern Indonesia. Accordingly, efforts to reduce its prevalence should prioritize improvements in maternal health services, stronger family planning programs, prevention of infectious diseases, and better access to basic sanitation in rural communities.